The Development of Modern Architecture and Its Role in Society - Siddiqova Madinabonu (Lembaga Yasin AlSys, 2026)
This article examines the characteristics of modern and historical architectural monuments, emphasizing their roles in societal life and the interconnections between them within contemporary urban environments. Historical monuments are analyzed as cultural and aesthetic assets that embody collective memory and identity, with particular attention to approaches to their preservation and restoration as key strategies for sustaining cultural heritage. In parallel, modern architecture is explored through the lenses of technological advancement, functionality, ecological sustainability, and inclusivity, highlighting how contemporary design solutions respond to current social and environmental demands. The analysis focuses on how historical heritage and modern architectural interventions can be harmonized to enhance the aesthetic quality, functional efficiency, and cultural vitality of urban spaces. The findings underscore that balanced integration of conservation principles with innovative design promotes sustainable and creative development in architecture, supports the continuity of cultural narratives, and strengthens the social and experiential dimensions of the built environment.